2009
DOI: 10.1093/wjaf/24.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Trembling Aspen Removal Effects on Lodgepole Pine in Southern Interior British Columbia: Ten-Year Results

Abstract: Manual cutting treatments are routinely applied to release lodgepole pine (Pinus contorta var. latifolia Engelm.) from trembling aspen (Populus tremuloides Michx.) competition in southern interior British Columbia. We studied the effects of this treatment on pine and an aspen-dominated community on three sites in the Interior Douglas-Fir and Montane Spruce biogeoclimatic zones. After 10 years, when stands were 17–20 years old, treated aspen was significantly shorter than control aspen, and treated pine had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In keeping with similar published results on single manual brushing of deciduous broadleaf competition (Simard 1990;Heineman et al 2009), a measurable improvement in the vigor and size of young Douglas-fir can be expected on zonal sites in the Mixed Broadleaf-Shrub Vegetation Complex. The Forestry Chronicle Downloaded from pubs.cif-ifc.org by 44.224.250.200 on 09/12/21 For personal use only.…”
Section: Brushing and Stand Productivitysupporting
confidence: 87%
See 2 more Smart Citations
“…In keeping with similar published results on single manual brushing of deciduous broadleaf competition (Simard 1990;Heineman et al 2009), a measurable improvement in the vigor and size of young Douglas-fir can be expected on zonal sites in the Mixed Broadleaf-Shrub Vegetation Complex. The Forestry Chronicle Downloaded from pubs.cif-ifc.org by 44.224.250.200 on 09/12/21 For personal use only.…”
Section: Brushing and Stand Productivitysupporting
confidence: 87%
“…3) or vertical canopy competition. An alternative broadleaf competition measure that considers only broadleaf densities that are as tall as or taller than the crop trees, has been promoted to integrate with BC's free growing regulations (Heineman et al 2009;Newsome et al 2012). However, this approach does not consider the "smaller than" component of broadleaf competition, stand density and canopy composition (Harper 2017) and, effectively truncates the vertical dimension of the competition neighbourhood and the lower competition intensity distribution where maximum response is correlated (Wagner 2000;Simard et al 2005;Harper 2015).…”
Section: Predicting Douglas-fir Size From Broadleaf Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…However lodgepole pine growth responses to reduction in neighboring aspen density have been variable in other south-central to southern BC studies. According to Heineman et al (2008), the average aspen density threshold was 1867 sph and pine stem diameter declined above this density level while Newsome et al (2008) reported that 1000 sph of tall aspen was the threshold density on a sub-boreal spruce dry-warm and (SBSdw1) and interior Douglas-fir dry-cool (IDFdk3) biogeoclimatic zone in south-central British Columbia. In another study Newsome et al (2004) reported that neither diameter nor any other metric of lodgepole pine growth improved within four years after different density reductions on an IDFxm (very dry mild) site.…”
Section: Permanent Sample Plotsmentioning
confidence: 99%
“…They also require practical ways of using this information to develop cost-effective treatment prescriptions. Up until now, little work has been initiated to identify competition thresholds for aspen-lodgepole pine mixtures to describe where pine survival or growth is significantly impacted (Heineman et al, 2008;Newsome et al, 2003Newsome et al, , 2006Newsome et al, , 2008Newsome et al, , 2010 or canopy light availability is reduced to critical levels (Comeau, 2001;Comeau et al, 2006). Thus there is a need for further investigation to describe aspen-lodgepole pine competitive aspects in central BC forests.…”
Section: Introductionmentioning
confidence: 99%